Aunt Jane Of Kentucky - Hall, Eliza Calvert (Book collections on Project MUSE., 2015)
""You see, some folks has albums to put folks' pictures in to remember them by, and some folks has a book and lorites down the things that happen every day so they won't forget them; but, honey, these quilts is my albums and my diaries.""Aunt Jane is a fictional character well known for her gentle folk wisdom and her vivid descriptions of a picturesque and almost vanished way of life in the rural South of the last century. Her words recall lavish Sunday dinners, courtships, quilting bees, church meetings, and county fair competitions. Yet Aunt Jane of Kentucky is more than a collection of rem.